Urban Elites and Mass Transportation : the Dialectics of Power. - Whitt, J. Allen, 1940- (Princeton : Princeton University Press, 2014)
In an unusually systematic approach to the study of urban politics, this study compares three different models of political power to see which can best explain the development of the Bay Area Rapid Transit System in San Francisco and the attempts of Los Angeles to build a comparable system. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these impor.
Print version record.
Cover; Acknowledgments.
eBooks on EBSCOhost
Keywords: Urban transportation -- California; Local transit -- California; Elite (Social sciences) -- California; Community power; Transports urbains -- Californie; Transports publics -- Californie; Élite (Sciences sociales) -- Californie; Pouvoir communautaire; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Community power; Elite (Social sciences); Local transit; Urban transportation; California